Mechanical characterization of fiber reinforced Polymer Concrete - Reis,João Marciano Laredo dos (2005)
A comparative study between epoxy Polymer Concrete plain, reinforced with carbon and glass fibers and commercial concrete mixes was made. The fibers are 6 mm long and the fiber content was 2% and 1%, respectively, in mass. Compressive tests were performed at room temperature and load vs. displacement curves were plotted up to failure. The carbon and glass fibers reinforcement were randomly dispersed into the matrix of polymer concrete. An increase in compressive properties was observed as function of reinforcement. The comparison also showed that Polymer Concrete, plain and reinforced, has a better performance than regular market concrete, suggesting that PC is a reliable alternative for construction industry.